Implementasi Nilai Gotong-Royong Dalam Kehidupan Bermasyarakat di Perum YKP Pandugo II - Kinanti R Hayati; Agges Brian Darmawan; Helga Maritza Putri; Izzuddin Ahmad Faza (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The waning application of the value of gotong royong in social life is the background of this research. While the values in the culture of gotong royong play an important role in uniting the nation, this study aims to describe the implementation of cooperatives, discuss the factors that hinder its implementation, and efforts to maintain a mutually beneficial culture of gotong royong. The type of methodology used in this research is qualitative, and the data collection techniques used include direct observation, interviews, and documentation. The results show that the culture of gotong royong still exists in PERUM YKP PANDUGO II, but some residents are not involved in cooperative activities and are not in accordance with their environment. This shows that the value of gotong royong is starting to disappear over time. This has a negative impact on people's lives, with an increase in individualism and a decrease in the sense of kinship, kinship, brotherhood, justice, volunteerism, responsibility, gotong royong, and the active role of individuals, as well as unity and integrity in people's lives and environment.